2018
DOI: 10.1590/s1984-29612018004
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the accuracy of different laboratory methods for the diagnosis of intestinal parasites from stray and domiciled cats (Felis catus domesticus) in Goiânia, Goiás, Brazil

Abstract: Cats are carriers of zoonotic agents to humans, including intestinal parasites. The purpose of this study was to analyze the accuracy of different laboratory methods for the diagnosis of intestinal parasites. Fecal samples were processed by the Willis, Sheather, Faust and Hoffman-Janer-Pons-Lutz (HJPL) methods. Accuracy analysis was performed determining the sensitivity, specificity, positive and negative predictive value and Kappa. A total of 149 fecal samples were collected, 65 from stray cats and 84 from do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 17 publications
0
5
0
2
Order By: Relevance
“…Analysis of 237 fecal samples from domestic cats using the three coproparasitological techniques revealed that 93 (39.2%) samples were positive for one or more parasitic structures, observing a higher frequency of parasites such as Ancylostoma spp., G. intestinalis , P. illiciens and Cystoisospora spp. This occurrence can be classified as moderate, as the prevalence in recent coproparasitological studies in cats in the country varied between 17% and 75.26% ( Campos et al, 2016 ; Lima et al, 2018 ; Quadros et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of 237 fecal samples from domestic cats using the three coproparasitological techniques revealed that 93 (39.2%) samples were positive for one or more parasitic structures, observing a higher frequency of parasites such as Ancylostoma spp., G. intestinalis , P. illiciens and Cystoisospora spp. This occurrence can be classified as moderate, as the prevalence in recent coproparasitological studies in cats in the country varied between 17% and 75.26% ( Campos et al, 2016 ; Lima et al, 2018 ; Quadros et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence rates of T. gondii infection in cats in most of Asia are generally lower than the world average, such as 19.6% in Kuwait (Abdou et al 2013), 30.4% in Iraq (Switzer et al 2013), 24.5% in China (Ding et al 2017;Li et al 2022), 2.2 to 47.2% in Korea (Hong et al 2013;Jung et al 2017), 4.8 to 11% in Bangkok (Jittapalapong et al 2010Sukhumavasi et al 2012), 40% in Iran (Sharif et al 2009), 14.5% in Malaysia (Wana et al 2020), 9 to 26.7% in Japan (Matsuu et al 2017;Kyan et al 2021) and18.7% in Thailand (Huertas-López et al 2021). For countries in Americas, the prevalence rates were 8 to 84.4% in Brazil (Cavalcante et al 2006;Bastos et al 2014;Magalhães et al 2017;Lima et al 2018), and 6 to 66.7% in the United States (Lilly et al 2013;Ballash et al 2015;Scorza and Lappin 2017). As the soul mate of humans, cats are inextricably linked to people's daily lives.…”
Section: Catmentioning
confidence: 99%
“…A avaliação da precisão de diferentes técnicas parasitológicas permite determinar a concordância e a reprodutibilidade para aplicação em laboratórios (Lima et al, 2018).…”
Section: Hoffman Sheather Coloraçãounclassified